Endothelial deletion of the cytochrome P450 reductase leads to cardiac remodelling - Lopez, Melina; Malacarne, Pedro F.; Ramanujam, Deepak P.; Warwick, Timothy; Müller, Niklas; Hu, Jiong; Dewenter, Matthias; Weigert, Andreas; Günther, Stefan; Gilsbach, Ralf; Engelhardt, Stefan; Brandes, Ralf P.; et al. (Frontiers in Physiology, 2022)
The cytochrome P450 reductase (POR) transfers electrons to all microsomal cytochrome P450 enzymes (CYP450) thereby driving their activity. In the vascular system, the POR/CYP450 system has been linked to the production of epoxyeicosatrienoic acids (EETs) but also to the generation of reactive oxygen species. In cardiac myocytes (CMs), EETs have been shown to modulate the cardiac function and have cardioprotective effects. The functional importance of the endothelial POR/CYP450 system in the heart is unclear and was studied here using endothelial cell-specific, inducible knockout mice of POR (ecPOR-/-). RNA sequencing of murine cardiac cells revealed a cell type-specific expression of different CYP450 homologues. Cardiac endothelial cells mainly expressed members of the CYP2 family which produces EETs, and of the CYP4 family that generates omega fatty acids. Tamoxifen-induced endothelial deletion of POR in mice led to cardiac remodelling under basal conditions, as shown by an increase in heart weight to body weight ratio and an increased CM area as compared to control animals. Endothelial deletion of POR was associated with a significant increase in endothelial genes linked to protein synthesis with no changes in genes of the oxidative stress response. CM of ecPOR-/- mice exhibited attenuated expression of genes linked to mitochondrial function and an increase in genes related to cardiac myocyte contractility. In a model of pressure overload (transverse aortic constriction, TAC with O-rings), ecPOR-/- mice exhibited an accelerated reduction in cardiac output (CO) and stroke volume (SV) as compared to control mice. These results suggest that loss of endothelial POR along with a reduction in EETs leads to an increase in vascular stiffness and loss in cardioprotection, resulting in cardiac remodelling.